A Rescue Technique for Intraoperative Proximal Migration of a Nellix Stent During Endovascular Aneurysm Sealing. (June 2016) - Torella, Francesco; Scurr, James R. H.; Barkat, Mo; Fisher, Robert K.; McWilliams, Richard G.
Purpose: To describe a technique to rescue intraoperative migration of 1 of the 2 Nellix stents during endovascular sealing of abdominal aortic aneurysms (EVAS).Technique: The technique requires advancement and inflation of a 10-mm angioplasty balloon into the inlet of the migrated stent via an upper limb approach. Inflation of the balloon allows completion of EVAS without risking the contralateral endobag occluding the inlet of the migrated stent.Conclusion: This technique allows safe completion of EVAS without compromising stent patency or aneurysm seal and should be considered when intraoperative migration of a Nellix stent occurs despite appropriate precautions.